THE EFFICACY OF GAMIFICATION IN ENHANCING VOCABULARY ACQUISITION AMONG SECONDARY LEVEL ESL LEARNERS - Umaraliyev Mukhriddin (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the intersection of Ludic Pedagogy and Second Language Acquisition (SLA). As traditional rote memorization faces criticism for low engagement levels, gamification—the application of game-design elements in non- game contexts—offers a promising alternative. This study examines how digital platforms such as Kahoot! and Quizlet impact lexical retention and student motivation.